Distomolar Supernumerary in the mandibular ramus associated with a dentigerous cyst. A case presentation - Denia Morales Navarro; José Ángel Méndez Capote (Universidad de Ciencias Médicas de La Habana, 2018)
Introduction: Supernumerary teeth are anomalies in which there is an increase of the normal dental formula.  They occasionally cause complications, such as the formation of a dentigerous cyst.  Because of the unusual finding, and even more because of the report of this association, a case presentation is carried out. Objective: To describe the management of a supernumerary distomolar in the mandibular ramus associated with a dentigerous cyst, making emphasis on the importance of the preoperative imaging studies and the endo-buccal surgery approach. Case presentation: 34 years old female patient from whom the third molars were removed during adolescence, who presented facial cellulitis 3 months before the molars removal, which was a reason to perform an orthopantomography.  Then, a molar in the mandibular ramus was detected. During oral examination, a light vestibular table expansion in the left mandibular ramus was found.  The presence of a dental structure from the molar group which was associated with a radiolucent area was confirmed by orthopantomography, and was also confirmed by CT-scan.  Exeresis of both molars under general anesthesia was planned, with an endo-buccal approach. There were no complications. The patient was discharged 24 hours later, and was treated in the outpatient consulting room for 6 months.  Histopathological diagnosis revealed the presence of a cyst. Conclusions: The finding of a supernumerary distomolar tooth in the mandibular ramus associated with a dentigerous cyst is an infrequent clinical situation that allows to make good use of the benefits of digital imaging studies, and implement a treatment plan that ends in a successful exeresis via an endo-buccal route, without any complications.  Keywords:supernumerary tooth, tooth not erupted, dentigerous cyst, successful exeresis.